2007
DOI: 10.1016/j.ijdevneu.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term histological outcome after post‐hypoxic treatment with 100% or 40% oxygen in a model of perinatal hypoxic–ischemic brain injury

Abstract: Hypoxic newborns have traditionally been given supplemental oxygen, and until recently, guidelines for neonatal resuscitation recommended that 100% oxygen be used. Exposure to 100% oxygen after hypoxic injury, however, may exacerbate oxidative stress. The current study evaluated the effect of exposure to 100, 40 or 21% oxygen after neonatal hypoxic-ischemic injury on the severity of brain injury after long-term survival. The severity of histological brain injury was not different in animals exposed to 100% oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…We chose 30 min of reoxygenation because this is a typical resuscitation time used clinically. In contrast to our results, other investigators found no difference in brain injury in rats after reoxygenation with 100% oxygen vs. air (29), or even reduced injury after 100% oxygen in mice (30). Of note, the results in the latter study may have been distorted because more animals in the 100% O 2 group died prematurely and were excluded from the analyses.…”
Section: Articlescontrasting
confidence: 99%
“…We chose 30 min of reoxygenation because this is a typical resuscitation time used clinically. In contrast to our results, other investigators found no difference in brain injury in rats after reoxygenation with 100% oxygen vs. air (29), or even reduced injury after 100% oxygen in mice (30). Of note, the results in the latter study may have been distorted because more animals in the 100% O 2 group died prematurely and were excluded from the analyses.…”
Section: Articlescontrasting
confidence: 99%
“…To our knowledge, it is the first study to examine the effect of hyperoxia after HI on long-term injury development in gray and white matter in a neonatal rat model using manganeseenhanced MRI in combination with DTI and anatomical imaging. Although some experimental studies have found no effect (10) or that hyperoxia limits injury (11), mounting experimental data indicate that hyperoxia exacerbates injury after HI in the immature brain (5,12). Our study corroborates these findings and adds important knowledge to the effect of hyperoxia on the prolonged evolution of injury in gray and white matter.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…air, 39 or even reduced injury after 100% oxygen in mice. 40 Importantly, more animals in the 100% group died prematurely and were excluded from analyses in the latter study.…”
Section: Histopathologymentioning
confidence: 97%
“…A neuroprotective effect of hypothermia has been shown in both newborn animals 155, 157, 291 and clinical trials 19,39,163,164 . In line with these studies we demonstrate a protective effect of therapeutic hypothermia across all three models in the present work:…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
See 1 more Smart Citation